The Demand for Money in Thirteen European and Non-European Countries: A Tabular Survey - M. M. G. Fase; J. B. Kuné (Kredit und Kapital, 1975)
Die Geldnachfrage in 13 europäischen und außereuropäischen Ländern Die Studie gibt einen Überblick (S. 414 ff.) über die bedeutendsten Untersuchungen zur Geldnachfrage in zehn europäischen Ländern sowie in Australien, Kanada und Japan. Nicht berücksichtigt werden Beiträge über die Vereinigten Staaten und Entwicklungsländer. Außerdem haben sich die Autoren auf vierteljährliche Zeitreihenanalysen beschränkt. Die Tabelle enthält die wesentlichsten Darstellungen der erwähnten Untersuchungen. – – The demand for the money in 13 European and non-European countries This study gives a survey (pp. 414) of the most important money studies on demand for money carried out for ten European countries, Australia, Canada and Japan. Excluded are the contributions on the United States and the developping countries. Furthermore the authors confined themselves to time series analyses based on quarterly data only. The tabular survey lists the most important features of the reported studies.
Keywords: 330